1998
DOI: 10.1136/adc.78.1.40
|View full text |Cite
|
Sign up to set email alerts
|

New chart to evaluate weight faltering

Abstract: A new chart was designed to aid accurate identification of weight faltering and failure to thrive. It provides guidance on the lower limits of expected weight gain for children, whatever their initial centile position. The chart's theoretical basis, the process of its construction, and its evaluation are described in this paper.Evaluation was by a self completion questionnaire, where respondents answered questions about a range of standardised growth patterns, plotted on old and new charts. Forty five health v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 10 publications
(7 reference statements)
0
13
1
Order By: Relevance
“…Three centile spaces = 2 SD scores. From 6 weeks onwards, there is less variability, and only 5% of children will cross through two intercentile spaces between then and the age of 1 year,6and only 1% will cross three centile spaces 7. This guidance applies only to contemporary standards (UK 1990) because earlier standards show substantial variations compared with present weight gain patterns 8.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three centile spaces = 2 SD scores. From 6 weeks onwards, there is less variability, and only 5% of children will cross through two intercentile spaces between then and the age of 1 year,6and only 1% will cross three centile spaces 7. This guidance applies only to contemporary standards (UK 1990) because earlier standards show substantial variations compared with present weight gain patterns 8.…”
Section: Definitionmentioning
confidence: 99%
“…This guidance applies only to contemporary standards (UK 1990) because earlier standards show substantial variations compared with present weight gain patterns 8. An additional problem is that very large and small infants regress to the mean: 5% of children on the 98th centile will fall through three centile spaces, whereas only 1% of children on the 2nd centile will fall through two 7. If one does not allow for this, an excess number of large babies will be identified as having FTT, and very small children will be missed.…”
Section: Definitionmentioning
confidence: 99%
“…For clinical purposes the adjustment has been incorporated into a specialist growth chart ( Fig. 1; Wright et al 1998a).…”
Section: The Definition Of Failure To Thrivementioning
confidence: 99%
“…has been explored, the extent to which health practitioners understand them and can use them 112 effectively is not clear. The layout and format of the chart may be important; a study in the 113 UK demonstrated that changing the chart format improved the precision of judgment made 114 about slow weight gain in infancy (Wright, Avery, Epstein, Birks, & Croft, 1998). 115…”
Section: Introduction 75mentioning
confidence: 99%